Paradigma dalam Arkeologi Maritim - Mundardjito, Mundardjito (Wacana, Journal of the Humanities of Indonesia, 2007)
This paper is based on a maritime archeological research that grounds itself on the preservation of archeological artefacts and maritime culture. Research on a number of drowned ships at the bottom of the sea and their cargo reveals the relationship between maritime culture and living regional communities. As a new paradigm in maritime archeology, its aim needs to be commensurate with the aim of the conservation efforts which is the empowerment of the communities themselves, and the communities outside of them, and needs to be oriented toward the interests of identity nurturance, development, and economy.